Role Of Gut Microbiota In Liver Regeneration: Analysis Of Hepatic Structural Changes And Extracellular Matrix Component After Partial Hepatectomy In Mice - Amin bin Abdul Rahman (Universiti Sains Islam Malaysia, 2024)
Matric :3181281 (FPSK)-Restricted until Aug'24